2007
DOI: 10.1017/s0030605307001102
|View full text |Cite
|
Sign up to set email alerts
|

Human disturbance affects habitat use and behaviour of Asiatic leopard Panthera pardus in Kaeng Krachan National Park, Thailand

Abstract: Edge effects arising from road construction and other development in protected areas can negatively affect the behaviour of wildlife, particularly large carnivores. The Asiatic leopard Panthera pardus is a large carnivore that may be sensitive to edge effects. Camera trapping was used to assess the influence of human disturbance along forest edges on leopard behaviour and habitat use in a 104 km 2 area of Kaeng Krachan National Park, Thailand. A minimum of four male and two female leopards was recorded in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 25 publications
7
61
2
1
Order By: Relevance
“…Upon release, males continued to move away from buildings, while females, after initial increase, generally decreased distance to building over time. Results coincide with the behaviour of reintroduced elephants in DGR that selected areas away from buildings (De Hoog 2014) and other species in several studies elsewhere that avoided human activities (Ngoprasert et al 2007;Vanthomme et al 2013), suggesting that human settlement was perceived as a disturbance by lions and elephants reintroduced to the reserve. While initial responses of females were to move away from buildings, the decrease in distance over time likely indicates their habituation to the disturbance which was not observed in males.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Upon release, males continued to move away from buildings, while females, after initial increase, generally decreased distance to building over time. Results coincide with the behaviour of reintroduced elephants in DGR that selected areas away from buildings (De Hoog 2014) and other species in several studies elsewhere that avoided human activities (Ngoprasert et al 2007;Vanthomme et al 2013), suggesting that human settlement was perceived as a disturbance by lions and elephants reintroduced to the reserve. While initial responses of females were to move away from buildings, the decrease in distance over time likely indicates their habituation to the disturbance which was not observed in males.…”
Section: Discussionsupporting
confidence: 78%
“…We expected movement rates to be highest upon release, decrease over the study period and eventually stabilize, together with an initial increase in distances from the release site during exploration and stabilization or reduction when the animals had settled. An increase in distances from buildings over time was expected in avoidance to human disturbances, a factor found to influence carnivore behaviours in various studies (Kerley et al 2002;Ngoprasert et al 2007). We also compared movements at different times of the day to test if forced dispersal increases diurnal activities of lions due to the need to explore the environment and avoid previously released conspecifics.…”
Section: Introductionmentioning
confidence: 95%
“…Livestock density outside of the forests was extremely high at 342 animals per km 2 and density of wild prey was at 56 animals per km 2 in the forested areas indicating the high prey biomass that is potentially available to the leopards in the landscape [60]. Also, an extensive network of rivers and ground vegetation provided by tea bushes explains the lack of influence of the distance to rivers and forest patches on habitat selection as reported in other studies [61,62]. Our study also found that built-up areas and agricultural lands show lower usage by leopards.…”
Section: Discussionmentioning
confidence: 89%
“…Understanding these issues requires long term data sets; often gathered by observation (5)(6)(7)(8)(9), with the help of VHF collars (1, [10][11][12][13][14][15][16] or more recently sourced from GPS collars (17)(18)(19)(20)(21). GPS collars can record data 24/7 for months or even years, in any terrain or conditions, at lower cost and without the bias inherent with observational studies.…”
Section: Introductionmentioning
confidence: 99%